Physiotherapy Management on Anterior Cruciate Ligament (ACL) Reconstruction: A Case Report - Pande Komang Ute Ketiga; Ferdi Perdana Putra (Universitas Udayana dan Diaspora Taipei Medical University, 2021)
Introduction: Anterior Cruciate Ligament (ACL) is one of knee’s ligaments that serves as a passive stabilization of the knee joint, to prevent excessive anterior tibia translation. On the medical management of an ACL tear, will be reconstructed with a surgical procedure, to graft the ACL using tendon tissue to restore joint fixation and stabilization, this surgery can be done with arthroscopy. In the post-reconstruction conditions, appropriate physiotherapy management is needed to reduce the risk of complications such as swelling, decreased joint range motion, muscle weakness, decreased balance and functional activity. Therefore, in this case, we discuss the early management of physiotherapy in cases of ACL reconstruction. Case Report: The patient was a male of 25 years who suffered a complete tear of the right ACL. He underwent an arthroscopically aided reconstruction 2 weeks after the injury with hamstring autograft. After 1 weeks, he visited the physiotherapy clinic and at the time had trouble bending and straighten the knee, his thigh muscles seemed to shrink, and difficulty to walk. Rehabilitation is carried out one session a day, six days a week, included exercise to improve ROM, strength, and gait training. Conclusion: This case suggests the exercise program provided can increase the range of motion of the knee joint after ACL reconstruction. Results of this case suggest a need for continued research with a larger group of patients with long-term evaluation is necessary to evaluate the safety and efficiency of exercise program in this case.